2010
DOI: 10.1039/c0ob00073f
|View full text |Cite
|
Sign up to set email alerts
|

Tricarbonyl M(I) (M = Re, 99mTc) complexes bearing acridine fluorophores: synthesis, characterization, DNA interaction studies and nuclear targeting

Abstract: New pyrazolyl-diamine ligands with acridine derivatives at the 4-position of the pyrazolyl ring were synthesized and characterized (L1 and L2). Coordination towards the fac- [M(CO) ). The interaction of the novel pyrazolyl-diamine ligands (L1 and L2) and rhenium(I) complexes (Re1 and Re2) with calf thymus DNA (CT-DNA) was investigated by a variety of techniques, namely UV-visible, fluorescence spectroscopy and circular and linear dichroism. Compounds L1 and Re1 have moderate affinity to CT-DNA and bind to DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 32 publications
4
42
0
Order By: Relevance
“…Finally, a few examples of localization in the nucleus (compounds 10,11, Figure 3) can also be found [54,55]. It should be noted that for compound 10, the luminescence comes from acridine rather than from the Re core.…”
Section: Re(i) Tricarbonyl Complexes With Specific Cell Localizationmentioning
confidence: 98%
“…Finally, a few examples of localization in the nucleus (compounds 10,11, Figure 3) can also be found [54,55]. It should be noted that for compound 10, the luminescence comes from acridine rather than from the Re core.…”
Section: Re(i) Tricarbonyl Complexes With Specific Cell Localizationmentioning
confidence: 98%
“…These results suggest that the 111 In‐DOTA effects in DNA are predominantly mediated by indirect mechanisms associated with the radiolysis of water, whereas 111 In‐ER3AO causes DNA damage by a combination of both direct and indirect mechanisms. The presence of the acridine‐orange‐based DNA intercalating moiety in the ER3AO conjugate could explain the direct auger electrons effect as a result of the tight interaction between the coordinated radiometal and DNA, as others have previously demonstrated …”
Section: Methodsmentioning
confidence: 74%
“…Santos et al. showed that a Re tricarbonyl complex containing a pyrazolyldiamine chelator‐bearing acridine derivative and its “hot” analogue 99m Tc are internalized significantly and are retained in the nuclei of B16F1 murine melanoma cells . So far, only a few reports have been published that deal with the cellular localization of rhenium tricarbonyl complexes in tumor cells, showing that a variety of complexes are internalized and accumulate in cytoplasmic organelles, but only a small number reaches the nucleus.…”
Section: Resultsmentioning
confidence: 99%